An Audit of the Academic Information System of UIN Sunan Kalijaga - Rahmaani, Amalia Ratna; Fauzi, Muhammad Dzulfikar; son, Sumarsono (IJID (International Journal on Informatics for Development), 2016)
Academic Information System (AIS) is a form of information technology in the form of software services in the education process including academic information. To get a good AIS services, it needs good governance, including IT support, service for IT users as well as continuity of care. Sunan Kalijaga UIN has adequate information technology support used in academic services for users. Audit SIA is needed to fit the IT governance framework and standards of Control Objectives for Information and Related Technology (COBIT). COBIT is standard because it is the most complete guide of best practices in IT management because it has a very good compromise in the breadth of coverage and detail of management's processes. Referring to one of the domains in COBIT is to Deliver and Support the domain that has the focus in his ministry. This study has implemented almost all IT activities and has a maturity level of 2.56, which means IT Academic Information System is approaching Defined Process management. This suggests that the activities of the Deliver and Support domain have been applied, but have not had formal procedures in writing and well documented.